Improving the Reliability of Bootstrap Tests with the Fast Double Bootstrap - Russell Davidson; James G. MacKinnon (Queen's University, Department of Economics, 2006)
We first propose two procedures for estimating the rejection probabilities of bootstrap tests in Monte Carlo experiments without actually computing a bootstrap test for each replication. These procedures are only about twice as expensive (per replication) as estimating rejection probabilities for asymptotic tests. We then propose a new procedure for computing bootstrap P values that will often be more accurate than ordinary ones. This "fast double bootstrap" is closely related to the double bootstrap, but it is far less computationally demanding. Simulation results for three different cases suggest that this procedure can be very useful in practice.
Keywords: C12; C15; 330; bootstrap test; double bootstrap; Monte Carlo experiment; rejection frequency; fast double bootstrap; FDB